PENGARUH CULTURE SHOCK DAN ADVERSITY QUOTIENT TERHADAP KEPUASAN KERJA TENAGA KERJA INDONESIA (TKI) DI HONGKONG - Muhammad Iqbal; Anggit Verdaningrum (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2016)
The purpose of this research is to investigate the influence of culture shock and adversity quotient to work satisfaction of Indonesian Labor Forces in Hong Kong. This quantitative research includes multiple regression analysis with 111 respondent. The sampling technique is using Nonprobability Sampling. Purposive Sampling with sample criteria: Indonesian citizen who works in Hogkong, female, working in domestic sector, has been working for a minimum of 6 months in Hongkong. Her age must be 20 years old or older, and she must have an education at least of an Elementary School level. Measurement for Culture Shock the result of the adaptation of Mumford, the measurement for Adversity Quotient the result of a modification of Rachmawati, and the measurement for work satisfaction is the result of the adaptation of Minnesota Satisfaction Questionare (MSQ) Short Form scale. According to analysis from the double regression analysis of the Anova tabl 8.837 Fb and Ft 3.08. so that F count > F table e , we got p= 0.000 ( p < 0.05), R= 0.140. Research hypothesis is accepted.Keywords: culture shock, adversity quotient, job satisfaction, TKIAbstrakPenelitian ini bertujuan untuk mengetahui pengaruh culture shock dan adversity quotient terhadap kepuasan kerja TKI di Hongkong. Penelitian kuantitatif ini melibatkan analisis regresi berganda dengan subjek sebanyak 111 responden. Teknik pengambilan sampel dengan Non Probability Sampling. Sampling Purposive dengan criteria sampel: Warga Negara Indonesia yang bekerja di Hongkong, perempuan, bekerja pada sektor rumah tangga, minimum lama bekerja di Hongkong 6 bulan, usia minimal 20 tahun, dan pendidikan minimal SD. Alat ukur culture shock yang digunakan dalam penelitian ini merupakan hasil adaptasi dari alat ukur milik Mumford, alat ukur adversity quotient merupakan hasil modifikasi milik Rachmawati, dan alat ukur kepuasan kerja merupakan hasil adaptasi skala Minnesota Satisfaction Questionare (MSQ) Short Form. Berdasarkan analisis regresi berganda pada tabel Anova didapatkan Fh 8.837 dan Ft 3.08. sehingga F hitung > F tabel, dan nilai Sig. 0.000 (p<0.05) R= 0.140. Hipotesis penelitian diterima.Kata Kunci: culture ahock, adversity quotient, kepuasan kerja, TKI